Synthesis of Titanium Oxide Nanoparticles Using Root Extract of Kniphofia foliosa as a Template, Characterization, and Its Application on Drug Resistance Bacteria. (5th May 2020) - Bekele, Eneyew Tilahun; Gonfa, Bedasa Abdisa; Zelekew, Osman Ahmed; Belay, Hadgu Hailekiros; Sabir, Fedlu Kedir
Abstract : Biogenic methods of synthesis of nanoparticles (NPs) using plant extracts have been given a great attention due to its nontoxicity and environmental friendliness. In this study, TiO2 NPs were synthesized from titanium tetrabutoxide and extract of root of Kniphofia foliosa . NPs of TiO2 were biosynthesized at different volume compositions of titanium tetrabutoxide to the plant extract with a ratio of 1 : 2, 1 : 1, and 2 : 1, respectively. These green synthesized NPs of TiO2 were characterized by thermogravimetric analysis (TGA/DTA), X-ray diffraction (XRD), scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS), transmission electron microscopy (TEM), ultraviolet-visible spectroscopy (UV-Vis), and Fourier transform infrared (FTIR) spectroscopy. TGA/DTA analysis has confirmed that the synthesized NPs of TiO2 were stable above the temperature of 500°C. The sharp and intense peaks at 2 θ values of 25.3, 38.0, 47.9, 53.2, 54.8862, 62.7, 70.2, and 75.0 have confirmed formation of crystalline NPs of TiO2 in the sample of 1 : 1 and 2 : 1 ratios, and less crystalline samples for TiO2 NPs prepared in a 1 : 2 ratio. Comparison between FT-IR absorption bands of the plant extract and that of calcined NPs of TiO2 confirmed the purity of synthesized nanomaterials, except unavoidable adsorption of moisture on the surface of TiO2 NPs in an open air. The antibacterial activity of biosynthesized TiO2 NPs and that of ethanolic root extract of Kniphofia foliosa was investigated via the disc diffusion method against human pathogen bacteria strains of Staphylococcus aureus, Escherichia coli, Klebsiella pneumonia, and Streptococcus pyogenes . Among the different ratios, TiO2 (1 : 1) NP shows better performance towards Gram-negative bacteria due to its smaller average crystalline size and uniform morphology observed in SEM image relative to the other two ratios of TiO2 NPs. Antibacterial activity of the ethanolic root extract of Kniphofia foliosa itself showed better performance towards Gram-negative bacteria than NPs of TiO2 that might be due to antibacterial activity of residue of ethanol left with the plant extract.